The Factor Of The Number Of Poor Population, Income Per Capita Population, And The Price Of Rice Substitution Of Raskin (Poor Rice) Demand In Pidie Religionin Using Statistik Model (The Estimation And The Korelation) - Jayanti, Ery (JOURNAL OF ECONOMIC SCIENCE, 2015)
This research focuses on the field of factors affecting demand RASKIN (poor rice) is an analysis of variety variables such as the number of poor population, income per capita population, and the price of rice substitution. Thus, the alteration of those variables enable occur change in the demand for RASKIN (poor rice).The purpose of this research is to investigate how far the affect of independent variable such as the number of poor population, income per capita population, and the price of rice substitution of RASKIN (poor rice) demand in Pidie religion. In addition, another purpose of this research is to investigate how the demand the development of RASKIN (poor rice) in Pidie district.The data used in this research is the secondary data was the result of survey in 2013 from Statistics central Agency (BPS) and Affairs Logistics Agency (BULOG) in Aceh province. The analysis model used is the model of multiple linear regression methodusing SPSS application.The result of this research indicates that RASKIN (poor rice) demand by the population of Pidie district influenced by the number of poor population, per capita income population, and rice prices tend to be more expensive substitutes. This is proved by R2 = 0, 0196, the level of alpha conviction is 90%. The third partial variables also influence with each other. Variables affecting the number of poor people in poor rice demand is proved by the T â (count) hitung of 3,129 is greater than 1588 compared with T- table. The level of alpha conviction is 90%, income the number of poor partially also affect poor rice demand is proved by the t 0.063 and tables for 1588. For the price of rice substitution proved by t 1576 smaller than T-table 1, 888 and significant at alpha 90%.